Prototype worlds of video games - Alejski , Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2021)
In this paper the author analyzes the phenomenon of prototype worlds – synthetic environments of simulators, video games and other types of software – used to conduct experiments at the level of user sensorium, environmental physics and social design. The author presents the evolution of the concept, beginning with Buckminister Fuller’s World Game project, moving through media experiments in the field of game design, and finally presenting contemporary applications (such as a drone pilot training project for the U.S. Air Force) and their implications.